Complement proteins are elevated in blood serum but not CSF in clinical high-risk and antipsychotic-naïve first-episode psychosis - Cropley, Vanessa; Kittel, Maximilian; Heurich, M.; Föcking, M.; Leweke, F. Markus; Pantelis, C. (Brain, behavior and immunity, 2023)
Alterations in the complement system have been reported in some people with psychotic disorder, including in pre-psychotic individuals, suggesting that complement pathway dysregulation may be a feature of the early psychosis phenotype. Measurement of complement protein expression in psychosis has been largely restricted to the blood from patients with established illness who were taking antipsychotic medication. The present study examined a range of complement proteins in blood and cerebrospinal fluid (CSF) derived from individuals at clinical high-risk for psychosis (CHR), antipsychotic-naïve first-episode psychosis (FEP) and healthy controls. A panel of complement proteins (C1q, C3, C3b/iC3b, C4, factor B and factor H) were quantified in serum and matched CSF in 72 participants [n = 23 individuals at CHR, n = 24 antipsychotic-naïve FEP, n = 25 healthy controls] using a multiplex immunoassay. Analysis of covariance was used to assess between-group differences in complement protein levels in serum and CSF. Pearson’s correlation was used to assess the relationship between serum and CSF proteins, and between complement proteins and symptom severity. In serum, all proteins, except for C3, were significantly higher in FEP and CHR. While a trend was observed, protein levels in CSF did not statistically differ between groups and appeared to be impacted by BMI and sample storage time. Across the whole sample, serum and CSF protein levels were not correlated. In FEP, higher levels of serum classical and alternative grouped pathway components were correlated with symptom severity. Our exploratory study provides evidence for increased activity of the peripheral complement system in the psychosis spectrum, with such elevations varying with clinical severity. Further study of complement in CSF is warranted. Longitudinal investigations are required to elucidate whether complement proteins change peripherally and/or centrally with progression of psychotic illness.